1996
DOI: 10.1002/aic.690420519
|View full text |Cite
|
Sign up to set email alerts
|

Study of instabilities in film blowing

Abstract: Bubble instabilities observed in film blowing using four different polyolefins are discussed: high-density polyethylene (HDPE), low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), and polypropylene (PP). Special attention is given to the effect of the frost line height on the bubble stability, an effect mostly ignored in the literature. A video-camera system was used to record the bubble shape and oscillations. In general, three forms of instabilities and combinations were observed: (1) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 13 publications
3
44
0
Order By: Relevance
“…The bubble is stable in this space for 2.2 < BUR < 3. This was in agreement with Ghaneh-Fard et al [9] who found that at low constant MDD ratio the bubble was stable at low frost line heights for a range of BURs. This particular FLH showed the smallest window of stable conditions.…”
Section: Bubble Stabilitysupporting
confidence: 82%
See 3 more Smart Citations
“…The bubble is stable in this space for 2.2 < BUR < 3. This was in agreement with Ghaneh-Fard et al [9] who found that at low constant MDD ratio the bubble was stable at low frost line heights for a range of BURs. This particular FLH showed the smallest window of stable conditions.…”
Section: Bubble Stabilitysupporting
confidence: 82%
“…The analysis of bubble stability in film blowing has largely focused on PEs (HDPE, LLDPE and LDPE), mainly due to their superior melt strength in comparison to other polymers such as PP. Only recently have results been reported on the bubble stability of PP [9]. Ghaneh-Fard et al [9] studied the bubble stability of PP and found PP to have a much smaller stable operating window in comparison to PEs.…”
Section: Background and Theorymentioning
confidence: 97%
See 2 more Smart Citations
“…There have been many theoretical attempts and experimental observations on this process over last four decades due to its academic and industrial importance (Han and Park, 1975;Kanai and White, 1984;Cain and Denn, 1988;Ghaneh-Fard et al, 1996;Yoon and Park, 2000;Doufas and McHugh, 2001;Fang et al, 2005;Zhang and Lafleur, 2008;Pirkle and Braatz, 2010). Especially, various theoretical issues including stability and sensitivity as well as multiple base flows have been explored for elucidating intricate phenomena occurring in film blowing systems (Hyun et al, 2004;Shin et al, 2007;Pirkle and Braatz, 2010).…”
Section: Introductionmentioning
confidence: 98%